Gazelles and muppets in the city: Stock market listing, risk sharing, and firm growth quantiles - Cosimo Abbate; Alessandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Financialization is persuading academics and policy-makers that the growth of SMEs can be unleashed by promoting their quotation on stock markets. Is that true? Answering this can give clues on the functions that stock markets actually perform in the financialized world. The market may allow collecting finance for productive investments, or mainly provide firms with opportunities for value extraction. It may work as a selection device or as a risk-sharing mechanism. In this paper, we test hypotheses linking the shape of the firm growth rates distribution to stock market functions, through quantile regressions. We use a sample of UK manufacturing companies listed on AIM, a junior segment of the London Stock Exchange, and comparably small and young unlisted companies. We find that the operating revenues and total assets of AIM-listed gazelles grow faster than for their unlisted peers, after controlling for lagged values of size, age, and growth. Yet, there is a loss reinforcing effect for companies listed on the AIM. After controlling for endogeneity by estimating instrumental variable quantile treatment effect (IVQTE), our findings dismiss the existence of a treatment effect of public quotation and are consistent with the stock market attracting relatively risky companies.
Keywords: 330; Firm growth; Quantile regression; Stock market; Financialization